Ethnobotanical study of Cymbopogon citratus (DC) Stapf. (Lemongrass) in Northern Morocco: Traditional uses and phytochemical composition - Maataoui, Jaber; Abduljaber, Malek; W Bussmann, Rainer; Khaddor, Mohamed (Ethnobotany Research and Applications, 2026)
Background: Cymbopogon citratus (Lemongrass) offers a variety of medicinal, recreational, culinary, and cosmetic benefits to consumers worldwide, largely shaped by local traditions and ways of life. However, little research has explored how people in Northern Morocco utilize this plant, and its chemical composition in the region has seldom been documented. Methods: A questionnaire was developed to assess awareness, use, cultivation, and storage of lemongrass and was administered through face-to-face interviews with 46 residents of the Tangier metropolitan area. Quantitative data were analyzed descriptively, and qualitative responses were examined using thematic analysis. The chemical composition of a local lemongrass sample was determined by gas chromatography–mass spectrometry (GC-MS). Results: Two-thirds of participants were aware of lemongrass, with about 56% using it in their diets and one-third cultivating it. The most common use involved mixing it with other ingredients to prepare Moroccan tea, home-cooked meals, or traditional remedies for colds, flu, and digestive discomfort. GC-MS analysis revealed 25 distinct components, with geranial (34.47%), neral (28.96%), and α-myrcene (18.8%) as the major constituents. Conclusions: The use of Cymbopogon citratus in Northern Morocco aligns with cultural practices observed elsewhere in Africa and Asia. The chemical composition supports its traditional medicinal applications and suggests opportunities for commercialization that could benefit both the local economy and traditional medicine. This study lays the groundwork for future comparative analyses of lemongrass use worldwide, offering insights for policymakers and scientists interested in sustainable and culturally grounded medicinal plant utilization. Keywords: Cymbopogon citratus, Lemongrass, Consumer Use, Survey Research, Morocco, Chemical composition, Ethnobotany